Speed control of switched reluctance motors based on fuzzy logic controller and MATLAB/Simulink - Hayder Salim Hameed; Qasim Al Azze; Mohammed Saadi Hasan (Institute of Advanced Engineering and Science, 2023)
Switched reluctance motors (SRM) becomes increasingly popular due to its simple structure and dependability. It seems to have a two-pole configuration. A stator had also centralized coils along each pole, whereas a rotor has an iron core only. As a result, the switched reluctance motor is anticipated to be a low cost, incredibly robust variable-speed machine. Because the switched reluctance motor is only made up of laminated coils, its performance is heavily reliant on the magnetic properties of the core material. Vibration, torque ripple, and low torque for each unit volume are some of their drawbacks. Typically, a standard proportional-integral-derivative (PID) controller is designed to regulate the Switched Reluctance Motor's speed. Furthermore, the PID controller could also regulate and control SRM when the load changes abruptly. A fuzzy logic controller (FLC) is utilized within this article to regulate the speed of the SRM drive. The MATLAB/Simulink platform is used to analyze the behavior of SRM with FLC. To demonstrate FLC's superiority, its results have been compared to that of a typical PID controller.